2017
DOI: 10.1155/2017/7670521
|View full text |Cite
|
Sign up to set email alerts
|

Shortest-Way: An Improved Empirical Transition Method for Signal Coordination

Abstract: Four fundamental insights into transition methods are provided from the perspective of traffic engineers. An improved empirical transition method (i.e., Shortest-way) is developed with the goal of reducing the time spent on offset correction and the offset deviations of the coordinated phases during the transition period. Shortest-way operates stepwise and can be activated to correct offset at the scheduled time to switch plans. The maximum amount of adjustment that can be made to a transition cycle length is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…TRANSYT (Hale [106]) is the most popular of these control methods. Because traffic demand usually varies over time, the Time-Of-Day (TOD) mode is often used, which consists of a collection of distinct signal plans for different times of the day, such as peaks and off-peaks (Zheng et al [107]). On the other hand, robust signal optimization is used to deal with traffic flow uncertainty, i.e., a scenario-based technique is used in order to ensure the performance of fixed-signal systems (Zhang et al [108]).…”
Section: Fixed-time Traffic Signal Controlmentioning
confidence: 99%
“…TRANSYT (Hale [106]) is the most popular of these control methods. Because traffic demand usually varies over time, the Time-Of-Day (TOD) mode is often used, which consists of a collection of distinct signal plans for different times of the day, such as peaks and off-peaks (Zheng et al [107]). On the other hand, robust signal optimization is used to deal with traffic flow uncertainty, i.e., a scenario-based technique is used in order to ensure the performance of fixed-signal systems (Zhang et al [108]).…”
Section: Fixed-time Traffic Signal Controlmentioning
confidence: 99%
“…Ants define this value, depending on their type (AntD, AntF, and AntE) to obtain the attractiveness of their neighbour points in the solution space as expressed in (16), in which is the objective function that corresponds to the ant type , pow, pow = ( , pow, pow) .…”
Section: Selection and Evaluation Of Pathsmentioning
confidence: 99%
“…At the end of the iteration, the trail evaporates based on (16), where is the pheromone evaporation coefficient.…”
Section: Updating Pheromonementioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that the transition between signal timing plans could have either positive or negative impacts, causing increases or decreases in the level of services [7][8][9][10]. Positive impacts are associated with right traffic signal transition strategies and include benefits such as minimum travel time and stops which minimise delays, fuel consumption, and gas emissions.…”
Section: Introductionmentioning
confidence: 99%